PADILLA, Carlos René & SCOTT, Lindy. Terrorism and the war in Iraq. A Christian Word from Latin America. Buenos Aires: Ediciones Kairos, 2004, 186 p. - Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2011)
PADILLA, Carlos René & SCOTT, Lindy. Terrorism and the war in Iraq. A Christian Word from Latin America. Buenos Aires: Ediciones Kairos, 2004, 186 p.